(3GdQLGds - (3GdfLGTj , CMeO Hf Ydj Hf CMeO Hf GdYHGS GdGSOj, CHh GdYHGS (B- (3GHf Gdchaj,J (B450 (3g` s
(3ChdgG (B:s
[(3hHYO(B] (3aEfj deG hbaJ Ydi eG PcQg GdSjO GdTQja ef JYHjQ bhe ef eNGdajfG Gfg dGSda Hce hdG eUfa hbO LeYJ ef Pdc eG ESJWYJ hde CHdZ ZGjJg s
(3BNQgG (B:s
(3jfJgj HCKfGA HGH BOe s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B317s
(3agQS GdWH (B- (3GdLRA (B1 - (3U (B556 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B188 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs